2022
DOI: 10.55142/jogser.1207910
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Beden Eğitimi ve Spor Dersine Yönelik Tutumları ile Okula Yönelik Tutumları Arasındaki İlişki

Abstract: Bu araştırmada, ortaokul öğrencilerinin beden eğitimi ve spor dersine yönelik tutumları ile okula yönelik tutumları arasındaki ilişkinin ortaya çıkarılması amaçlanmıştır. Araştırmanın verileri nicel yöntemlerle elde edilmiştir. 451 ortaokul öğrencisi araştırmanın örneklemini oluşturmuştur. Araştırmada Güllü ve Güçlü (2009) tarafından geliştirillen beden eğitimi ve spor dersine yönelik tutum ölçeği ile Alıcı (2013) tarafından geliştirilmiş okula yönelik tutum ölçeği kullanılmıştır. Araştırmada aritmetik ortalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Hazar et al [42] and Duman [46] reported that the physical education course attitudes of students who have an athlete license are high. In another study, it was seen that secondary school students interested in sports had more positive attitudes towards PEL [47]. It can be seen as a natural consequence of this situation that students with a sportive background have a high attitude towards PEL.…”
Section: Discussionmentioning
confidence: 93%
“…Hazar et al [42] and Duman [46] reported that the physical education course attitudes of students who have an athlete license are high. In another study, it was seen that secondary school students interested in sports had more positive attitudes towards PEL [47]. It can be seen as a natural consequence of this situation that students with a sportive background have a high attitude towards PEL.…”
Section: Discussionmentioning
confidence: 93%